Від вибору бізнес-ідеї до її реалізації - Болтянська, Лариса Олексіївна; Болтянская, Лариса Алексеевна; Boltianska, Larysa; Тебенко, Віта Миколаївна; Тебенко, Вита Николаевна; Tebenko, Vita (Мелітополь: ТДАТУ, 2017)
UK: Основою будь-якої прибуткової діяльності є ефективна бізнес-ідея. Якщо бізнес-ідея визнається прийнятною до впровадження, наступним етапом її життєвого циклу є складання ділового плану, чи бізнес-плану, як його заведено називати в підприємницький практиці. Діловий план являє собою своєрідну модель майбутнього бізнесу. При його розробці враховуються всі можливі витрати на реалізацію бізнес-ідеї, перевіряються майбутні схеми виробничо-комерційної діяльності, обґрунтовуються можливі схеми фінансування процесів створення нововведення і т.п. EN: The basic and important stage of realizing the dream of entrepreneurship is a well-chosen business idea. When choosing a business idea, the entrepreneur-beginner should clearly understand the purpose and objectives of the future activity, have an idea of the ways and means of achieving it and their solutions. The success of the implementation of a business idea depends on the chosen sphere of activity, the organizational-legal form of small business, strategy and tactics of management. In a developed market, success can only come to someone who brings something new to his business, different from the ones offered by competitors. The emergence of business ideas is a creative process. It can be stimulated by creating a creative search atmosphere and gaining new knowledge about business. If the business idea is recognized as acceptable for implementation, the next stage in its life cycle is the preparation of a business plan, or a business plan, as it is called in business practice. The business plan is a peculiar model of future business. In its development, all possible costs for the implementation of business ideas are taken into account, future schemes of production and commercial activity are checked, possible schemes of funding for innovation processes, etc., are substantiated. The development of a business plan, therefore, should become a kind of filter for dropping out ideas that can not be realized under any circumstances. Potentially, in any business is a hidden mass of opportunities. Those who find them and use them competently seem to be more likely to achieve a positive result. But if planning is carried out in accordance with the logic of business ideas development, then its consequences will be not only the improvement of the quality of business, but also its transformation into life, which, besides material wealth, provides also a great pleasure from their own business.
From selection of business idea to its realization
Keywords: бізнес-ідея; власна справа; сфера діяльності; бізнес-планування; рекомендації; business idea; own business; sphere of activity; business planning; recommendations